The Effect of the Deterioration of the Sudanese Currency on the Collapse of the Sudanese Economy In the period (2015-2021) - د. رشيدة عباس العوض محمد صالح (White Nile Journal for Studies and Research, 2024)
The aim of the research was to determine the impact of the deterioration of the Sudanese currency on the collapse of the Sudanese economy in the period (2015) and 2021), and to reveal the social, economic and political reasons for the deterioration of the Sudanese currency. The research problem included: What are the reasons that led to the deterioration of the Sudanese currency? Does increasing inflation rates lead to a decline in the value of the currency? The local currency, of the Sudanese currency, and the increase in inflation were among the reasons that le to the collapse of the study period. There is a direct relationship between the deterioration of the local currency and inflation rates - the deterioration of the local currency process leads to inflation. The higher the inflation rate, the greater the deterioration of the currency, and I said that we research, the necessity of following a financial and monetary policy that works to Hiding a shelf avoids a deterioration in the rationalization of public spending in the country. Words to the campaign, Al- Haniyat Economy.